2007
DOI: 10.1002/humu.9488
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of theHGSNATgene in Italian patients with mucopolysaccharidosis IIIC (Sanfilippo C syndrome)

Abstract: Mucopolysaccharidosis (MPS) describes any inherited lysosomal storage disorder resulting from an inability to catabolize glycosaminoglycans. MPS III (or Sanfilippo syndrome) is an autosomal recessive disease caused by a failure to degrade heparan sulphate. There are four subtypes of MPS III, each categorized by a deficiency in a specific enzyme involved in the heparan sulphate degradation pathway. The genes mutated in three of these (MPS IIIA, MPS IIIB, and MPS IIID) have been cloned for some time. However, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This mutation has been shown to cause exon skipping, thereby resulting in the deletion of a substantial portion of the protein [10]. The most common splice site mutation, c.234+1G>A, was identified in 7 patient families: 1 from France, 1 from Italy, 1 from Spain, 1 from Turkey, 2 from Morocco, and 1 from Canada (in which both parents are of Moroccan origin) [10, 18-21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation has been shown to cause exon skipping, thereby resulting in the deletion of a substantial portion of the protein [10]. The most common splice site mutation, c.234+1G>A, was identified in 7 patient families: 1 from France, 1 from Italy, 1 from Spain, 1 from Turkey, 2 from Morocco, and 1 from Canada (in which both parents are of Moroccan origin) [10, 18-21]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that transcripts carrying premature termination codons are rapidly degraded via the nonsense-mediated mRNA decay pathway, which protects the cell from potentially harmful effects of truncated proteins [22]. The p.R384 * mutation was detected in 10 patients from 6 different countries (Poland, Czech Republic, Italy, The Netherlands, Canada, and Turkey) [10, 18, 19, 21]. Feldhammer et al showed that these mutations had relatively high frequencies among MPS IIIC families and were also characterized by wide distribution, which did not suggest a founder effect in any particular population [19].…”
Section: Discussionmentioning
confidence: 99%
“… 20 Furthermore, the deleterious nature of nearly all known missense mutations can be established via their occurrence in amino acids present in a transmembrane domain and/or conservation among orthologs. 42 , 43 , 82 The protein and activity of the majority of the known missense mutations have been exogenously expressed in cell culture. 83 , 84 Transfection of 18 of these resulted in negligible HGSNAT activity, while the remaining four displayed protein and function comparable to those of wild type, and so are therefore currently considered clinically insignificant polymorphisms.…”
Section: Genetics Of Mps IIImentioning
confidence: 99%
“…The first 43 nucleotides were based on genomic sequence (GenBank accession number NG_009552.1), nucleotides 44 -202 were present in a spliced EST (DR000652.1) and nucleotides 203-1992 in mRNA sequence XM_372038.2. Direct amplification of the predicted full-length HGSNAT cDNA was, however, unsuc-cessful (5, 6) and further publications adopted the nomenclature where the second ATG was considered to be the initiation site (11)(12)(13)(14)21). In the current work we experimentally assessed which of the predicted sites initiates the synthesis of a functional protein.…”
Section: Hgsnat Can Use Either Of Its Two Atg Start Sites In Vitro Anmentioning
confidence: 99%